Catfish Epidermal Preparation Accelerates Healing of Damaged Nerve in a Sciatic Nerve Crush Injury Rat Model - Renno, Waleed M.; Afzal, Mohammad; Paul, Bincy; Nair, Divya; Kumar, Jijin; Al-Hassan, Jassim M. (Frontiers in Pharmacology, 2021)
Preliminary investigations showed that preparations from Arabian Gulf catfish (Arius bilineatus, Val) epidermal gel secretion (PCEGS) exhibit potent anti-inflammatory and healing properties as shown in our previous clinical trials for the healing of non-healing diabetic foot ulcers, chronic back pain, and some other neurological disorders. Here, we report for the first time a unique preparation containing only proteins and lipids (soluble protein fraction B, SPF-FB), derived from the PCEGS accelerated the healing and recovery of sensory-motor functions of experimental sciatic nerve crush injury in rats with its unique neuroprotective and neuroregenerative properties on the spinal neurons and peripheral nerve fibers. Male rats were randomly assigned to Five groups: (I) NAÏVE, (II) SHAM, (III) CRUSH treated with saline, (IV) CRUSH+SPF-FB treated with 3 mg/kg intraperitoneally (IP), and (V) CRUSH+SPF-FB treated with 6 mg/kg subcutaneously (SC) groups. The crush groups III, IV, and V underwent sciatic nerve crush injury, followed by treatment daily for 14 days with saline, SPF-FB IP and SPF-FB SC. All animals were tested for the neurobehavioral parameters throughout the 6 weeks of the study. Sciatic nerve and spinal cord tissues were processed for light and electron histological examinations, stereological analysis, immunohistochemical and biochemical examinations at Week 4 and Week 6 post-injury. Administration of SPF-FB IP or SC significantly enhanced the neurobehavioral sensory and motor performance and histomorphological neuroregeneration of the sciatic nerve-injured rats. The stereological evaluation of the axon area, average axon perimeters, and myelin thickness revealed significant histomorphological evidence of neuroregeneration in the FB-treated sciatic nerve crush injured groups compared to controls at 4 and 6 weeks. SPF-FB treatment significantly prevented the decrease in NeuN-immunoreactive neurons, decreased GFAP immunoreactive astrocytes, and increased GAP-43. We conclude that SPF-FB treatment lessens neurobehavioral deficits, enhances axonal regeneration following nerve injury. Further, SPF-FB protects spinal neurons and enhances subcellular recovery by decreasing astrocytic activity and GAP-43, thus improves nerve regeneration and functional recovery. SPF-FB preparation of the PCEGS contains the components necessary to protect the degenerating spinal cord neurons and enhancing the regeneration of injured sciatic nerve fibers following crush injury.